"The Structure of Antithesis in Animal Tales" - boudina, mehamed (El Omda in Linguistics and Discourse Analysis, 2018)
A reader of animal tales observes that they often depict a set of opposing dualities, the most prominent of which is the (intelligence – stupidity) pair, frequently reflecting (deception and being deceived), respectively. Deception is typically expressed through the weak and physically fragile animal, while the animal characterized by size and physical strength is the one that is deceived. Intelligence here signifies the power of the mind, which overcomes physical strength. When a conflict arises in an animal tale between two characters distinguished by strength and weakness, the weaker animal character often prevails. This paradox reflects the realities of life and the environment in which humans live. Ultimately, in these tales, the animal speaks on behalf of the individual, expressing the lived human experience.